Oxidative flavour chemistry and biochemistry in parsley - Channell, Guy Andrew (1996)
Deterioration of flavour quality during processing and storage is often brought about by oxidative processes. These typically involve oxygen or an active form of oxygen in effecting transformation of a wide range of volatile and non-volatile compounds, including key quality chemicals, flavour precursors and antioxidants. To investigate the nature of the chemical and biochemical change within vegetables and herbs, unblanched frozen parsley was selected as a suitable tissue.